Linking theory and practice : the case of TESL trainee teachers / Siti Salina Ghazali and Lee Lai Fong - Ghazali, Siti Salina; Lee, Lai Fong (Institute of Research, Development and Commercialization (IRDC), 2005)
The purpose pf this study was to investigate the TESL trainee teachers; insights on the link between theory and practice. This study also sought to find out how they viewed the effectiveness of the teacher preparation programme in terms of preparing them for teaching secondary school students. The study involved 79 TESL Part 7 and 8 trainee teachers from the Faculty of Education, UiTM selected through purposive sampling procedure. This in-depth study adopted both quantitaive and qualititative methods to ensure a wide coverage of areas and detailed explanations pf those area be gathered.